Reaching balance and sustainability: weight regulation in combat sports. A case study of a female boxer - Pettersson, S.; Pipping Ekström, M. (Reflective Practice. International and Multidisciplinary Perspectives, 2014)
Weight classification systems that operate in most combat sports often result in dietary restraint and preoccupation with body weight. The practice of rapid weight loss by severe reductions of food and fluid intake as well as sweat induced dehydration is prevalent. Research has demonstrated negative physiological, psychological and performance effects as an outcome of such practices, and sport governing bodies and medical associations have highlighted the importance of coming to terms with weight-making practices in combat sports. The aim of this paper is to provide insight into non-legislative ways of weight-making practices in boxing and consider this information with a sustainability lens. Two semi-structured interviews with a former world class female boxer concerning three phases during her career (novice, elite and coach) were conducted. The results of a content analysis demonstrate that irrespective of the boxing phase, the most prominent aspects in influencing weight regulation were knowledge, identity and balance. The phenomenon of weight regulation is not without contradiction however, and results suggest that structural changes (rules) within weight category sports should be considered.